Gravure Printing of Graphene for Large‐area Flexible Electronics. (29th April 2014) - Secor, Ethan B.; Lim, Sooman; Zhang, Heng; Frisbie, C. Daniel; Francis, Lorraine F.; Hersam, Mark C.
<x xml:space="preserve">Abstract</x> Gravure printing of graphene is demonstrated for the rapid production of conductive patterns on flexible substrates. Development of suitable inks and printing parameters enables the fabrication of patterns with a resolution down to 30 μm. A mild annealing step yields conductive lines with high reliability and uniformity, providing an efficient method for the integration of graphene into large‐area printed and flexible electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>